The animals who changed their colors - Allamand, Pascale (New York : Lothrop, Lee & Shepard, 1979)
The polar bear, whale, tortoise, and two crocodiles try to imitate the parrot's beautiful colors, only to discover how impractical they are.
3.0
K-3
K-3
School Library Journal
Keywords: Animals -- Fiction; Individuality -- Fiction